1978
DOI: 10.2307/3279509
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility of Biomphalaria tenagophila Populations to Infection with a Strain of Schistosoma mansoni

Abstract: Experiments to determine the susceptibility of Biomphalaria tenagophila from 20 localities over the species range exposed to a strain of Schistosoma mansoni showed widely varying infection rates, from 0% to 91.5%, this latter having been observed in a sample from an area where the natural infection rate of B. tenagophila has been the highest in the country. Comparison with similar studies involving B. glabrata seems to indicate that a process of adaptation between S. mansoni and B. tenagophila is evolving, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 5 publications
0
23
0
2
Order By: Relevance
“…The behavior of those snails to the possible infection with S. mansoni strain which infect naturally two different species of Biomphalaria is identical to the resistance observed with B. tenagophila from Puerto Hormiguero, on the Uruguay River in the province of Corrientes (Pellegrino et al 1968, Borda & Pellegrino 1976, Paraense & Correa 1978. This is the second opportunity that snails of that species were found naturally refractory to the infection in the province of Corrientes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The behavior of those snails to the possible infection with S. mansoni strain which infect naturally two different species of Biomphalaria is identical to the resistance observed with B. tenagophila from Puerto Hormiguero, on the Uruguay River in the province of Corrientes (Pellegrino et al 1968, Borda & Pellegrino 1976, Paraense & Correa 1978. This is the second opportunity that snails of that species were found naturally refractory to the infection in the province of Corrientes.…”
Section: Discussionmentioning
confidence: 55%
“…The susceptibility of B. tenagophila to infection with the SJ strain was demonstrated in 15 regions of Brazil (Paraense & Correa 1978). The infection rates varied between 0.8 and 91.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation (Paraense & Corrêa 1978) showed that 15 out of 20 populations of B. tenagophila from the species range were susceptible to S. mansoni from the Paraíba valley (sample SJ, from São José dos Campos). Comparing the relatively lower infection rate of those populations to those observed in B. glabrata exposed to the BH schistosome (from Belo Horizonte, state of Minas Gerais), we concluded that it might be understood "in the context of an ongoing process of adaptation of the tenagophilainfecting schistosome by selection through sucessive passages by the snail host".…”
Section: Biomphalaria Glabratamentioning
confidence: 99%
“…The susceptibility level of these different Biomphalaria species to infection by the same strain of S. mansoni varies greatly (Paraense & Corrêa 1973, 1978. Besides the difference in susceptibility observed between Biomphalaria species compatible with the parasite, some strain or geographical isolates of the same species of Biomphalaria also presented great variation in susceptibility to the parasite.…”
mentioning
confidence: 99%